Pengaruh Arang Cangkang Kelapa Sawit dan Pupuk MKP terhadap Karakter Morfofisiologi Tanaman Jagung di Tanah Aluvial - Aswin Harbarisnandar; Iwan Sasli; Tatang Abdurrahman (Politeknik Negeri Lampung, 2026)
The utilization of alluvial soils for expanding agricultural land to increase maize production is constrained by low soil pH and limited availability of macronutrients. The application of oil palm shell charcoal as a soil ameliorant has the potential to improve soil properties and enhance the effectiveness of MKP fertilizer as a source of phosphorus and potassium. This study aimed to evaluate the interactive effects of oil palm shell charcoal and MKP fertilizer on the growth and yield of maize grown on alluvial soil. The experiment was conducted in Limbung Village, Kubu Raya Regency, from September 2025 to January 2026 using a split-plot design arranged in a randomized complete block design with three replications. Oil palm shell charcoal (without and with charcoal) was assigned as the main plot, while MKP fertilizer rates (0, 50, 100, 150, and 200 kg ha⁻¹) were applied as subplots. Observed variables included vegetative growth, physiological characteristics, and yield components. The results showed that the combination of oil palm shell charcoal and MKP fertilizer significantly improved maize growth and yield. The application of oil palm shell charcoal combined with MKP fertilizer at a rate of 150 kg ha⁻¹ produced the highest and most efficient yield, with a dry shelled grain weight of 216.28 g plant⁻¹.